Retrospective comparative analysis of cardiovascular implantable electronic device infections with and without the use of antibacterial envelopes. Issue 3 (March 2017) - Hassoun, A.; Thottacherry, E.D.; Raja, M.; Scully, M.; Azarbal, A.
Summary: Background: Cardiovascular implantable electronic device (CIED) infections are associated with morbidity and mortality. Peri-operative systemic intravenous antibiotic prophylaxis reduces the rate of CIED infections. AIGISRx, a polymer envelope implanted with the CIED, releases minocycline and rifampin, and has been introduced to reduce infections. Methods: Retrospective review of 184 patients who underwent CIED implantation was conducted. Ninety-two patients were implanted with an AIGISRx envelope (AIGISRx group) and 92 patients were not implanted with an AIGISRx envelope (control group). Data were collected on demographics and risk factors for CIED infections (i.e. congestive heart failure, renal insufficiency, chronic kidney disease, oral anticoagulant use, chronic steroid use, need for lead replacement or revision, temporary pacing, early re-intervention, and having more than two leads in place). Rates of implantation success, major infections and mortality were compared between the AIGISRx group and the control group. Results: The AIGISRx group had longer hospitalizations (6.8 ± 10.7 days vs 3.1 ± 5.2 days; P  = 0.001), higher chronic corticosteroid use, higher rates of replacement or revision (51.1% vs 8.7%; P  = 0.001), and a greater proportion of devices with more than two intracardiac leads (42.4% vs 29.3%; P  = 0.03) than the control group. Successful implantation occurred in 97% of patients in both groups. Major infection was seen in 5.4% of cases in the AIGISRx group and 1.1% of cases in the control group ( P  = 0.048). Device removal was conducted in 3.3% of cases in the AIGISRx group compared with 1.1% of cases in the control group ( P  = 0.16). There were two deaths in the AIGISRx group. Organisms cultured were meticillin-resistant Staphylococcus aureus, meticillin-susceptible S. aureus and Enterococcus faecalis . Conclusion: The AIGISRx group had higher rates of major infection but also higher risk factors compared with the control group. The rate of device extraction and CIED-related mortality was higher in the AIGISRx group than in the control group.